To solve the quadratic equation by factoring, we want to rewrite it in the form of ax^2 + bx + c = 0. In this case, the equation is already in that form, so we can proceed with factoring.
First, let's rewrite the equation with all terms on one side:
12x^2 + 9x = 0
Next, we factor out the greatest common factor, which is 3x since both terms have it:
3x(4x + 3) = 0
Now we can set each factor equal to zero and solve for x separately:
3x = 0 or 4x + 3 = 0
For the first equation, divide both sides by 3 to solve for x:
x = 0/3
x = 0
For the second equation, subtract 3 from both sides and solve for x:
4x = -3
x = -3/4
So the solutions to the quadratic equation 12x^2 = -9x are x = 0 and x = -3/4.
Consider the following quadratic equation:
12x^2=−9x
Step 2 of 2 : Solve the quadratic equation by factoring. Write your answer in reduced fraction form, if necessary.
1 answer